Floodplain evaluation matrix FEM: A multiparameter assessment methodology. Issue 3 (13th April 2020) - Habersack, Helmut; Schober, Bernhard
Abstract: River floodplains allow for higher levels of conveyance and a greater capacity for floodwater, often improving the flood situation locally and regionally in hydrological and hydraulic terms. The European Floods Directive aims to protect existing and to restore potential floodplains to make use of their beneficial functions within an integrated plan of flood risk management. However, river floodplains are confronted with many other demands such as development of settlements, industry, and commerce and its supporting infrastructure. With such developments flood protection measures such as dykes and walls often follow restricting the floodplain's natural boundaries. To limit the loss of floodplains it is necessary to evaluate the importance of floodplains for flood risk management and to develop ultimately support tools for legal and spatial planning. This paper presents a method for evaluating and ranking river floodplains according to hydrological and hydraulic parameters and demonstrates its application at two very different Austrian river reaches. The results show which parameters and associated thresholds prove to be of greatest applicability to support future spatial planning strategies.